Do neurocritical care units improve outcomes for brain-injured adults: a protocol for a systematic review and meta-analysis. Issue 3 (16th March 2021) - Pham, Xiuxian; Ray, Jason; Serpa Neto, Ary; Udy, Andrew
Abstract : Introduction: Neurocritical care is a rapidly developing subspecialty within intensive care medicine which aims to improve outcomes of critically ill neurological patients. This has inspired the formation of specialised intensive care units or services to provide dedicated care of brain-injured patients, as well as new training pathways for physicians. However, expansion has been variable worldwide and it is yet to be determined if there are clear benefits in regard to patient outcomes. We are planning a systematic review with meta-analysis to assess whether the introduction of neurocritical care units or services, or neurointensivists have favourable effects on survival. Methods and analysis: We will include all observational and interventional studies comparing specialised neurocritical care units or services with general or non-specialised units in the care of acutely brain-injured adults. The primary outcome will be all-cause mortality at the longest follow-up, and secondary outcomes will be intensive care unit and hospital length of stay, and functional outcomes. All relevant studies will be identified through database searches. All study selection and data extraction will be conducted by two independent reviewers. We will conduct a random-effects meta-analysis to synthesise evidence for all outcomes. In addition, we will perform a subgroup analysis by disease process. We will assess confidence in the cumulative evidence using the Grading of Recommendations, Assessment, Development and Evaluations framework. Ethics and dissemination: This systematic review and meta-analysis does not require ethical approval. We will publish findings from this systematic review in a peer-reviewed scientific journal and present these at conferences. It will be included in the primary author's higher degree research thesis. PROSPERO registration number: CRD42020177190.